The Influence of Website Quality, Service Quality, and Price Perception on Repurchase Intention Mediated by Customer Satisfaction at PT Meratus Line - Annisa Nursoleha; Didik Junaedi Rachbini; Sugiyono (Indonesian Journal of Business Analytics, 2025)
This study investigates how customer satisfaction at PT Meratus Line mediates the effects of price perception, service quality, and website quality on repurchase intention. Customers are given questionnaires as part of the study's quantitative methodology, which uses partial least squares analysis. 105 participants completed the survey, and the respondents are patrons of the Jakarta branch of PT Meratus Line. SEM-PLS data analysis demonstrates that consumer happiness is positively and significantly impacted by website quality. Customer satisfaction is then positively and significantly impacted by both price perception and service quality. Repurchase intention is favorably and considerably influenced by customer satisfaction. Additionally, the relationship between price perception and repurchase intention and service quality is mediated by customer satisfaction, but website quality has no discernible impact.